Pengaruh Etos Kerja, Semangat Kerja dan Lingkungan Kerja Fisik Terhadap Kinerja Pegawai Pada Badan Pendapatan, Pengelola Keuangan dan Aset Daerah (BPPKAD) Kota Kediri - Pranasari, Shafa Afia Nanda Andya; Hidayati, Nur; Muttaqien, Zaenul (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study aims to analyze the influence of work ethic, work spirit, and physical work environment on employee performance at the Regional Revenue, Financial, and Asset Management Agency (BPPKAD) of Kediri City. This research employed an associative quantitative method with a descriptive approach. The population consisted of 215 employees, and a purposive sampling technique was used to select 100 respondents. Data were collected using a five-point Likert scale questionnaire that had been tested for validity and reliability. Data analysis was conducted through classical assumption tests and multiple linear regression analysis using SPSS version 26. The results indicate that work ethic, work spirit, and physical work environment have a positive and significant effect on employee performance, both partially and simultaneously. The coefficient of determination (R²) value of 0.693 shows that 69.3% of employee performance variation can be explained by the three independent variables. Therefore, improving employee performance at BPPKAD Kediri City can be achieved by strengthening work ethics, increasing work spirit, and creating a comfortable and productive physical work environment.